Collection of crop genetic resources in Italy, 2004 - Laghetti, G.=700 1 Miceli, F.; Cifarelli, S.; Hammer, K.
(Es, En, Pt)
ilus., 16 ref.
Keywords: RECURSOS GENETICOS; RECOLECCION; BIODIVERSIDAD; ITALIA; NOTICIARIO DE RECURSOS FITOGENETICOS